2010
DOI: 10.3233/nre-2010-0562
|View full text |Cite
|
Sign up to set email alerts
|

Potential driving issues in combat returnees

Abstract: The driving abilities of service members returning from Operation Enduring Freedom and Operation Iraqi Freedom (OEF/OIF) have not been well reported and are an important aspect of their return to normal life. This article reviews the unique risk factors for unsafe driving in this cohort. In particular, the cognitive and psychological symptoms of mild traumatic brain injury and postraumatic stress disorder, two of the most common diagnoses affecting these returning warriors, are specified, and their possible as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 48 publications
(42 reference statements)
0
30
1
Order By: Relevance
“…Moreover, participants who drove off base more frequently during deployment showed higher scores on the DSP than those who drove less frequently, and those who assumed both driver and passenger roles during deployment scored significantly higher than those who were only a passenger. Combat veterans have acknowledged that one of their postdeployment driving issues is unintentionally reverting to evasive or battlefield driving tactics in the civilian setting, which can result in considerable stress and aggressive behavior in driving (Killgore et al, 2008;Lew et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, participants who drove off base more frequently during deployment showed higher scores on the DSP than those who drove less frequently, and those who assumed both driver and passenger roles during deployment scored significantly higher than those who were only a passenger. Combat veterans have acknowledged that one of their postdeployment driving issues is unintentionally reverting to evasive or battlefield driving tactics in the civilian setting, which can result in considerable stress and aggressive behavior in driving (Killgore et al, 2008;Lew et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Although combat veterans were reportedly able to resume driving instantly on their reentry in civilian society (Lew et al, 2010), paramount to the subject matter is how long it may take for their postdeployment driving to return to normal. Our study revealed individual differences in the length of time required to resume normal driving in the civilian setting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aggressive driving contributes to over half of all motor-vehicle accident (MVA) fatalities and increased risk for MVA injuries (AAA Foundation for Traffic Safety, 2009). Although aggressive and risky driving behavior can result from many things (e.g., impulse control problems), research suggests that military training, warzone exposure, exposure to driving-related traumatic events, and postdeployment mental health problems (e.g., posttraumatic stress disorder [PTSD], posttraumatic brain injury [TBI] symptoms) contribute to aggressive and risky driving behaviors (Kuhn et al, 2010;Lew, Amick, Kraft, Stein, & Cifu, 2010). Several controlled studies have demonstrated the effectiveness of cognitive-behavioral and relaxation strategies for reducing aggressive and risky driving behaviors in civilian populations (Deffenbacher, Huff, Lynch, Oetting, & Salvatore, 2000;Deffenbacher, Filetti, Lynch, Dahlen, & Oetting, 2002;Galovski & Blanchard, 2002).…”
mentioning
confidence: 99%